2017
DOI: 10.3233/nre-162057
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of changes in gait performance over four years in persons with late effects of polio

Abstract: The small gradual reduction in gait performance over time in persons with late effects of polio is primarily determined by the individual variations in the knee flexor strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Among the variables, step length, measured at individuals’ regular walking velocity, showed the highest correlation with the RMS value obtained from the knee flexor during maximal flexion effort (R 2 = 0.1632, p < 0.0001). These results were plausible and consistent with previous reports, suggesting that knee flexion strength is an important predictor of gait performance [ 34 ]. Consistent with this observation, Mañago et al, discovered in their multivariable analysis that knee flexion strength remained a significant variable for predicting gait speed, whereas knee extension did not [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Among the variables, step length, measured at individuals’ regular walking velocity, showed the highest correlation with the RMS value obtained from the knee flexor during maximal flexion effort (R 2 = 0.1632, p < 0.0001). These results were plausible and consistent with previous reports, suggesting that knee flexion strength is an important predictor of gait performance [ 34 ]. Consistent with this observation, Mañago et al, discovered in their multivariable analysis that knee flexion strength remained a significant variable for predicting gait speed, whereas knee extension did not [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…The majority of longitudinal studies (14, 25, 104107) detect progressive muscle weakness, which contributes to deteriorating gait performance (107) and declining mobility (105). Quantifying the rate of decline in PPS is challenging and no reliable functional predictors have been validated.…”
Section: Resultsmentioning
confidence: 99%
“…The limitations in standing and walking, which increased the fall risk and caused emotional reactions of worry and fear of falling, underline the importance of understanding the impact on everyday activities and social participation. It has been shown that the decline in walking (using objective measures) develops slowly over time in people with LEoP [30,31]. Hence, by providing various targeted rehabilitation interventions, such as reducing LEoP-related impairments, adapting the home environment, prescribing appropriate aids and discussing strategies to achieve a good balance between rest and physical activity, walking ability may be sufficiently maintained.…”
Section: Methodological Considerations and Clinical Implicationsmentioning
confidence: 99%